2022
DOI: 10.1101/2022.07.05.22277281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and longevity of immune response to 3rd COVID-19 vaccine and effectiveness of a 4th dose in severely immunocompromised patients with cancer

Abstract: Cancer patients show increased morbidity with COVID-19 and need effective immunization strategies. We demonstrate that a 3rd dose of COVID-19 vaccine leads to seroconversion in 57% of patients that were seronegative after primary vaccination. The immune response is durable as assessed by anti-S antibody titers, T-cell activity and neutralization activity against wild-type SARS-CoV2 and BA1.1.529 at 6 months of follow up. A subset of severely immunocompromised hematologic malignancy patients were unable to moun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Even when fully vaccinated with a second boost dose, seroconversion rate in cancer patients was 88% and 70% for patients with solid tumors and hematologic malignancies, respectively (105). However, other studies have reported a lower seroconversion rate for patients with hematologic malignancies following vaccination which may improve with a third or a fourth vaccine dose (106,107). As those patients are at high risk of death if infected, they should avoid public exposure.…”
Section: Special Considerations For Vaccination Of Older Cancer Patie...mentioning
confidence: 99%
“…Even when fully vaccinated with a second boost dose, seroconversion rate in cancer patients was 88% and 70% for patients with solid tumors and hematologic malignancies, respectively (105). However, other studies have reported a lower seroconversion rate for patients with hematologic malignancies following vaccination which may improve with a third or a fourth vaccine dose (106,107). As those patients are at high risk of death if infected, they should avoid public exposure.…”
Section: Special Considerations For Vaccination Of Older Cancer Patie...mentioning
confidence: 99%